The neo-Roman conception of freedom in developmentalism: A historical perspective - Okello, Ayai Charles (School of Economics, 2026)
Does the statism of developmentalism have no regard for freedom? This paper re-examines political and theoretical premises of the developmentalist tradition in economics and argues that it embeds a conception of freedom known as neo-Roman freedom, distinct from that of the liberal tradition and more recently, the capability approach. To this end, the writings of four key periods/schools in the developmentalist tradition, that form the case studies of this paper, are reviewed. These are: Early Modern Europe, the American School, Meiji Japan and the Latin American School. While both the liberal tradition and capability approach focus on the individual as the primary unit of analysis, the neo-Roman conception views the freedom of the individual as derivative of the freedom of the collective, embodied by the state. Thus, this analysis – the legacy of the Roman Republic and the concept of the free state as formulated by Niccolò Machiavelli – sees in national sovereignty the path to securing individual freedoms. Also discussed is why developmentalism, through history, has aimed at industrialisation of countries in the periphery. This paper suggests that the answer is more political than economic, that is, industrialisation provides the material basis for national autonomy through the development of autonomous productive capabilities.